2018
DOI: 10.1093/jac/dky343
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of an OmpA inhibitor and colistin against colistin-resistant Acinetobacter baumannii: mechanistic analysis and in vivo efficacy

Abstract: We identified a novel class of antimicrobial agents that has proven to be effective in combination with colistin in an experimental model of severe infection by CST-R A. baumannii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Few mechanisms have been proposed to the underlying colistin resistance in Ab (Li et al, 2006;Adams et al, 2009;Falagas et al, 2010;Moffatt et al, 2010;Arroyo et al, 2011;Cai et al, 2012;Hood et al, 2013;Parra-Millán et al, 2018;Cafiso et al, 2019), however, no investigations have been conducted so far on the role that sRNAs exert on the biological adaptations of colistin resistance acquisition. Few studies have analyzed the sRNA contribution to the A. baumannii biology and antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Few mechanisms have been proposed to the underlying colistin resistance in Ab (Li et al, 2006;Adams et al, 2009;Falagas et al, 2010;Moffatt et al, 2010;Arroyo et al, 2011;Cai et al, 2012;Hood et al, 2013;Parra-Millán et al, 2018;Cafiso et al, 2019), however, no investigations have been conducted so far on the role that sRNAs exert on the biological adaptations of colistin resistance acquisition. Few studies have analyzed the sRNA contribution to the A. baumannii biology and antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…One of these peptides, a cyclic hexapeptide (AOA-2) lacking bactericidal or cytotoxic activities, was able to inhibit GNB adherence to host cells and biofilm formation, thereby preventing the development of infection in vitro and in a murine model of peritoneal sepsis [40]. A further study indicated that this OmpA inhibitor was effective in combination with colistin in an experimental model of severe infection with colistin-resistant A. baumannii strains [43]. This drug discovery program is considered as an initial stage of the development of a novel class of antimicrobial agents, and in this context, CarO emerges as an attractive target for drug design.…”
Section: Discussionmentioning
confidence: 99%
“…AOA-2, a cyclic hexapeptide as a blocking agent of AbOmpA without bactericidal activity decreases the adhesion of A. baumannii, Pseudomonas aeruginosa and E. coli to the surfaces of biotic and abiotic, and significantly enhances the sensitivity of A. baumannii to CST at the concentration of 125 μg/ mL. In vivo, the intraperitoneal injection of AOA-2 (10 mg/kg) in combination with CST (10 mg/kg) improved the survival rate of mice with bacteraemia by 20% [72,73]. In addition, some classic antimicrobial peptides (AMPs) interacting with AbOmpA have been gradually discovered, which are a series of endogenous defense peptides to kill bacteria and fungus [74][75][76].…”
Section: Therapeutic Strategies Targeting Abompa Polypeptidementioning
confidence: 99%